Sintering of Malaysian iron ore by using empty fruit bunch for iron making - Amrina binti Mohd Zakiyuddin (Kulliyyah of Engineering ,International Islamic University Malaysia, 2018)
Iron and steel industry is one of the highest carbon dioxide emissions contributors in global carbon dioxide emissions especially in sintering process. In order to reduce pollutant emissions from iron and steel industry, biomass has been widely proposed as an alternative cleaner and renewable fuel. In the iron sintering, it is desirable to substitute coke with biochar since this process contributes a huge amount of greenhouse gases. In this work, coke was substituted with biochar derived from oil palm empty fruit bunch (EFB) as an alternative fuel in the sintering of iron ore. However, process, condition and properties of EFB utilization to produce iron sinter are not established yet. Therefore, the effect of biochar content, temperature and reducibility of iron sinter were studied and examined. Biochar was produced from EFB at 450 °C at a heating rate of 10 °C/min, and held for 30 minutes. Sinter was first, prepared by mixing iron ore, biochar, and limestone with water as the binding agent in a ceramic bowl to produce green sample with various ratio biochar and iron ore with fixed 1% limestone. The sintering process was carried out by heating the dried green sample at various temperatures from 1050 °C to 1150 °C. The sinter was examined in terms of the apparent density, porosity, compressive strength and morphology. The sinter particles coalesce more at high sintering temperature but the porosity significantly decreased. In relation with the increasing heating temperature, the compressive strength and apparent density of the sinter had a significant increase at 1150 °C. The morphology shows that at high temperature, the dense sinter granules had been produced with decrement of larger pores and shaping into small pores. Thus, it is likely commensurate with the high compressive strength and low porosity of sinter granules. Meanwhile, the addition of biochar content has a detrimental effect on the properties of sinter. By increasing the biochar content attributed to the decrement of apparent density and compressive strength of the sinter. Apparently, the highest reducibility for the sinter that contains 5% of biochar content is 77.77%. The phase change suggested that at high temperature (1150°C) the sinter can be reduced to metallic iron. The utilization of biochar from EFB as an energy source for sintering of Malaysian iron ore is feasible to produce metallic iron for iron making process and reduce the CO2 emission simultaneously.